CSR ACTIVITIES IN THE CZECH SME SEGMENT - Metzker, Zdenko; Streimikis, Justas (International Journal of Entrepreneurial Knowledge, 2020)
The aim of the study is to find out the perception of the concept of corporate social responsibility (CSR) by the segment of small and medium-sized enterprises in the Czech Republic. In connection with the objectives of the study, a questionnaire survey was carried out on a sample of 419 respondents – business owners and managers. The data were collected from September 2019 to January 2020. χ2 and Z-score were used to assess the hypotheses. It was found that there were statistical differences in the perception of some aspects of the positive impact of the introduction of the CSR concept in case of monitoring responses based on the geographic scope of the business. The results showed that although the manager should take into account the ethical and moral implications of his decisions, less than half of the respondents are familiar with the concept of CSR and enforce it in their management practice and ultimately managers cannot identify positive benefits from CSR implementation – it declares positive answers whose values oscillate around 30%. The findings show that there are no statistically significant differences in the answers of managers depending on the size of the company - this proves that micro, small and medium enterprises, respectively their managers do not differ in their attitudes to the topic of CSR. The final effect of the paper is to show the perception of the concept of CSR of entrepreneurs - respondents in the Czech Republic.